Aggressive tumor recurrence after radiofrequency ablation for hepatocellular carcinoma - Kang, Tae Wook (Clin Mol Hepatol, 2017)
Image-guided radiofrequency ablation (RFA) is an evolving and growing treatment option for patients with hepatocellular carcinoma (HCC) and hepatic metastasis. RFA offers significant advantages as it is less invasive than surgery and carries a low risk of major complications. However, serious complications, including aggressive tumor recurrence, may be observed during follow-up, and recently, mechanical or thermal damage during RFA has been proposed to be one of the causes of this kind of recurrence. Although the exact mechanism of this still remains unclear, physicians should be familiar with the imaging features of aggressive tumor recurrence after RFA for HCC and its risk factors. In addition, in order to prevent or minimize this newly recognized tumor recurrence, a modified RFA technique, combined RFA treatments with transarterial chemoembolization, and cryoablation can be used as alternative treatments. Ultimately, combining an understanding of this potential complication of RFA with an understanding of the possible risk factors for aggressive tumor recurrence and choosing alternative treatments are crucial to optimize clinical outcomes in each patient with HCC.